Unlocking the potential: very-low-energy ketogenic therapy in obesity-related disorders - Daniel Simancas-Racines; Claudia Reytor-González; Ana Karina Zambrano; Giuseppe Annunziata; Angelo Michele Carella; Ludovica Verde; Evelyn Frias-Toral; Claudia V. Guerra; Ricardo Hidalgo (Food and Agricultural Immunology)
The Very Low-Energy Ketogenic Therapy (VLEKT) is a structured, multi-phase dietary regimen characterized by a carbohydrate intake of less than 50 g/day and a daily caloric intake of fewer than 800 kcal, which induces ketosis and facilitates significant weight loss. Evidence suggests that this nutritional therapy can improve glycemic control, lipid profiles, and blood pressure, making it a promising option for managing type 2 diabetes (T2D) and reducing cardiovascular risk. These benefits are achieved through reductions in triglycerides and low-density lipoprotein cholesterol (LDL-c), alongside increases in high-density lipoprotein cholesterol (HDL-c). However, the effects of the VLEKT on lipid metabolism remain controversial. The review emphasizes the urgent need for further research to validate the long-term safety and efficacy of the VLEKT. It also highlights the critical role of personalized dietary plans, supervised by healthcare professionals, to optimize health outcomes and address individual patient needs.